CREATION OF THE FIRST PRIVATE MILITARY AND SECURITY COMPANIES IN THE RUSSIAN FEDERATION (1998 – 2013) - KRYVYZIUK , Leonid; ONYSHCHUK, Oleksandr (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research. The author set himself the aim of researching and revealing the creation of the first Russian private military and security companies at the end of the 1990s, as a modern mercenarism phenomenon of previous generations. The research methodology is based on the general scientific principles of objectivity, systematicity and historicism. In the research there have been used general scientific methods: logical, analysis, synthesis, periodization and the others, as well as special methods of historical research: historical and genetic, historical and comparative, chronological. The scientific novelty of the obtained results consists in the comprehensive analysis of the creation process of the first private military and private security companies in the Russian Federation from the end of the 1990s to the beginning of the 2000s, their tasks, geography of activity, peculiarities of training and motivation of mercenaries. Conclusions. After analyzing the recent research and publications, it has been determined that the first among Russian private military and security companies at the end of the 1990s there were established “Orel-Antiterror”, “RIK”, “Ferax”, Moran Security Group, “RSB-Groupp”, Vega, “Slavyansky Corps” and “Wagner”. Private military and security companies became a very promising and attractive business. In fact, they became a tool in the hands of pro-government Russian oligarchic groups to satisfy their business interests both domestically and abroad. The emergnce of such structures has significantly expanded the ability of the Russian Federation to project its influence through military means in different regions of the world, in particular in Ukraine since 2014 and since 2015 in Syria, using hybrid influence and methods that the state cannot officially use. Private military companies were controlled by the Russian special services and staffed mainly by ex-servicemen from various power bodies and who had combat experience. Training of mercenaries was carried out in training centres and on military training grounds. Open or covert support of mercenaries, in particular financial, was provided by the state. The motivational factor for mercenaries was financial mainly. Key words: mercenarism, mercenary private army, private military company, private security company, Russian mercenaries.